The “Miss Curvy Uganda” pageant: representation, commodification and exploitation of women’s bodies - Francis Akena, Adyanga (Social Semiotics, 2020)
In early February 2019, Godfrey Kiwanda, a Uganda Junior Minister of Tourism proposed a beauty pageant dubbed, “Miss Curvy Uganda,” to publicly showcase voluptuous Ugandan women as means of attracting foreign tourists to generate more foreign currency earnings. The proposal drew sharp criticisms that appeared in the national media, ecumenical community gatherings, and public forums across the country. Feminists, ecumenical and cultural communities reviled the expressed opinion of the Junior Minister to commodify human bodies in the twenty-first century world. All the critics, motivated by moral and cultural arguments, agree that exploiting human, particularly female bodies, for generating revenue is reprehensible as the practice denigrates and debases humanity. This paper presents the paradox of the pageantry within the politics of patriarchy that exploits showcasing female bodies for generating revenue as well as the transformation of contemporary conscience in a neoliberal post-colonial economy.